Paus Fransiskus Merangkul Liyan - Permana, Aluisius Dian (Jurnal Teologi (Journal of Theology), 2020)
Human migration or displacement has become a never ending problems for some countries. Many people had fled from their home countries to find protection from war, oppression, and persecution. The humanitarian crisis raised from migration has become the attention of Pope Francis. Pope Francis is concerned because many people do not get protection or attention from destination countries and the world. In fact, many people died or did not get proper places. The accident that took place on the Lampedusa Coast tore the hearts of Pope Francis to call on the Church and countries not to stop paying attention to the problems migration. This paper discusses the contribution of Pope Franciss thoughts on migration. Pope Francis focused more human values and human dignity. In Evangelii Gaudium, Pope Francis discusses the social dimension of evangelism. The joy of the gospel should always be preached to all people especially those who are weak, poor, and excluded. The contribution of Pope Francis thought triggers us all to reflect on who our neighbors are and how we should behave towards our fellow human beings.